2018
DOI: 10.3892/mmr.2018.9539
|View full text |Cite
|
Sign up to set email alerts
|

An effective range of polydeoxyribonucleotides is critical for wound healing quality

Abstract: Wound healing is a physiological restorative response to tissue and cell injury. This process occurs in collaboration with a complex cascade of cellular events, including biochemical alterations to the extracellular matrix. Polydeoxyribonucleotide (PDRN) is a fragmented DNA mixture from Oncorhynchus mykiss or Oncorhynchus keta sperm known to promote tissue regeneration under different pathophysiological conditions. However, the most effective molecular size of PDRNs for promoting the wound healing process and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The wound healing properties of Ok-PDRN have also been assessed using several cell lines [ 8 , 26 , 27 , 28 ]. Ok-PDRN significantly increased the cell migration ability on all cell lines, including osteosarcoma cells, CDD-686sk, normal and diabetic human dermal fibroblasts (HDFs), and human umbilical vein endothelial cells (HUVEC).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The wound healing properties of Ok-PDRN have also been assessed using several cell lines [ 8 , 26 , 27 , 28 ]. Ok-PDRN significantly increased the cell migration ability on all cell lines, including osteosarcoma cells, CDD-686sk, normal and diabetic human dermal fibroblasts (HDFs), and human umbilical vein endothelial cells (HUVEC).…”
Section: Resultsmentioning
confidence: 99%
“…A total of nine studies have evaluated the wound healing activity of Ok- (six studies) and Om-PDRNs (three studies) [ 4 , 8 , 9 , 27 , 28 , 45 , 46 , 47 ]. In the case of Ok-PDRN, one study has evaluated the effective range of Ok-PDRN for wound healing as a function of molecular weight distributions (under 50 kDa, between 50 and 1500 kDa, over 1500 kDa) [ 27 ]. Regardless of MW distribution, daily i.p.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemistry revealed that the molecular weight of PDRN did not affect wound closure but did affect the quality of wound regeneration. 64 Among the examined sizes, mid-molecular-weight PDRN promoted earlier collagen deposition as well as better wound closure and increased re-epithelialization.…”
Section: Pdrn and Matrix Degradationmentioning
confidence: 93%
“…The drug was administered via subcutaneous and intracutaneous injections one time in 6 days along the periphery of the wound with a supplied 30G 0.3×13 mm needle (about 20 injections of 0.05 ml each). (14) The injections were made at a distance of 1 cm from the edge of the TU every 5 mm around the perimeter, distributing evenly the dose of the drug at the rate of 1 ml per 10 cm 2 of skin defect.…”
Section: Pdrn -Therapymentioning
confidence: 99%